2001
DOI: 10.1007/s001340000841
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of transient streptococcal bacteremia following urgent orotracheal intubation in critically ill patients

Abstract: Urgent intubation can cause transient bacteremia with streptococci in a significant proportion of intensive care patients. The observed frequency of bacteremia is higher than previously reported after elective intubation. The difficulty of intubation is probably a predisposing factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Serological correlation with specific bacteria and viruses, like C. pneumoniae or cytomegalovirus, lends additional support to the infection hypothesis (Saikku et al ., 1992; Chiu et al ., 1997; Blankenberg et al ., 2001; Danesh et al ., 2002). Transient bacteraemia due to real infections or artificial procedures, such as surgery or dental manipulation, together with trans ‐migration of microbiota into circulation, is well documented (Li et al ., 2000; Rijnders et al ., 2001; Chowers et al ., 2003). To a certain extent, bacteraemia is a physiological event that might occur during defecation or tooth cleaning.…”
Section: Discussionmentioning
confidence: 99%
“…Serological correlation with specific bacteria and viruses, like C. pneumoniae or cytomegalovirus, lends additional support to the infection hypothesis (Saikku et al ., 1992; Chiu et al ., 1997; Blankenberg et al ., 2001; Danesh et al ., 2002). Transient bacteraemia due to real infections or artificial procedures, such as surgery or dental manipulation, together with trans ‐migration of microbiota into circulation, is well documented (Li et al ., 2000; Rijnders et al ., 2001; Chowers et al ., 2003). To a certain extent, bacteraemia is a physiological event that might occur during defecation or tooth cleaning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rijnders et al (2001) looked at the incidence of bacteraemia following urgent intubation (n=68) in an adult medical ICU, and found 9% (6/68) of patients developed streptococcal bacteraemia immediately (mean 10.8 min) after urgent orotracheal intubation. This study demonstrated the development of transient bacteraemia (bacteria eliminated from the bloodstream within minutes) caused by a procedure that involves manipulation of the oral cavity in critically ill patients (Rijnders et al, 2001) and is one of few that has examined bacteraemia of oral origin in mechanically ventilated adults. Although the prevalence of bacteraemia in hospitalized patients as well as ICU patients has been described in the literature, the prevalence and oral care as an aetiology has not been examined specifically in mechanically ventilated adults.…”
Section: Increased Risk Related To Mechanical Ventilationmentioning
confidence: 99%
“…The collection of a baseline blood sample is included in the methodology of some studies of post‐intubation bacteraemia [4–6, 8, 9, 12–14, 16]. In the prophylaxis protocol for bacterial endocarditis published in 2004 by the British Cardiac Society and the Royal College of Physicians of London, it was decided not to evaluate those studies of bacteraemia of oral origin in which the methodology did not include taking a blood sample under basal conditions [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, this Society also recommended the administration of oral amoxicillin for ‘at‐risk’ dental procedures, regardless of whether this treatment was performed under local or general anaesthesia [3]. This absence of a consensus between the different expert committees regarding the significance of tracheal intubation as a risk factor for bacterial endocarditis may be explained by the different incidences of post‐intubation bacteraemia reported in the literature, which vary between 0% and 33% [4–16] (Table 1). However, very few authors have analysed the influence of the route of tracheal intubation in the production of bacteraemia.…”
Section: Major Studies Of the Incidence Of Bacteraemia After Tracheamentioning
confidence: 99%